NCOG-12. COGNITIVE FUNCTION (CF) & QUALITY OF LIFE (QOL) IN PATIENTS TREATED WITH PROCARBAZINE, CCNU, & VINCRISTINE (PCV) + RADIOTHERAPY (RT) VS. RT FOR ANAPLASTIC OLIGODENDROGLIOMA (AO) ON NRG RTOG TRIAL 9402. (12th November 2021) - Donovan, Laura; Won, Minhee; Cairncross, J Gregory; Iwamoto, Fabio; Buckner, Jan; Fink, Karen; Bahary, Jean-Paul; Hartford, Alan; Souhami, Luis; Nguyen, Timothy; Cescon, Terrence; Mishra, Mark; et al.
Abstract: BACKGROUND: PCV+RT substantially prolongs survival in AO patients, but long-term CF and QOL implications are unclear. We compared CF and QOL by treatment arm in RTOG 9402 participants and evaluated the impact that baseline characteristics had on CF, QOL, and survival. METHODS: CF and QOL were evaluated using the Mini Mental State Exam (MMSE) and Brain-Quality of Life (B-QOL) scale at baseline and annually. Scores were analyzed between treatment arms at each time point for patients with ≥ 10 years of follow-up data. Shared parameter models evaluated MMSE and B-QOL scores and survival for all patients. RESULTS: 42/148 (28.4%) participants in PCV+RT and 20/143 (14%) in RT alone arms survived ≥ 10 years. 35/42 and 39/42 (PCV+RT) and 18/20 and 17/20 (RT) participants completed baseline B-QOL and MMSE assessments, respectively. B-QOL scores did not differ between treatment groups at any time-point. Among 16 patients (10 PCV+RT, 6 RT) who completed year 10 MMSE evaluations, mean MMSE score at 10 years was higher in the RT arm (29.83 [95% CI 22.1, 30.0] vs. 26.50 [95% CI 29.4, 30.0], P= 0.04). Change in MMSE and B-QOL scores from baseline did not differ significantly between treatment groups at any time. In shared parameter models including all patients with baseline assessments, MMSE and B-QOL scores decreased over time (MMSE P = 0.0189, B-QOL P = 0.0005), but this did not differ by treatment group (MMSE P= 0.5727, B-QOL P = 0.3592). Younger age and higher KPS predicted better scores (MMSE P < 0.0001, P = 0.0002; B-QOL P = 0.0043, P = 0.0007). PCV+RT predicted better survival in both models. CONCLUSIONS: PCV+RT improves survival in AO. Shared parameter models show decrease in MMSE and B-QOL over time. However, relative to RT alone, the addition of PCV did not impact change in CF and QOL over time.